Studi Komparasi Tentang Batasan Khiyar Al-’Aib dalam Jual Beli Menurut Mazhab Syafi’i dan Hukum Perdata - Arwadi (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2017)
This study is a library research on “Comparative Study On Limitation khiyar Al-’Aib In the Sale and Purchase According to the Shafi’i of and Civil Law”. This study aims to find out the opinion of Shafi’i and the civil law of al-’Aib khiyar limits and the legal consequences arising and the similarities and differences between Shafi’i and civil law on limitation khiyar al-’aib in buying and selling. The similarities between Shafi’i and civil law is, equally allows for khiyar al-’Aib, the start time khiyar al-’Aib is since it was discovered by the buyer any defects and, if already rather old (after the discovery of defects), then right khiyar al-’Aib becomes void by the buyer and selling into luzum (fixed), while the difference is the language Shafi’i of his time is Fauri (direct) according to custom, civil law is “in a short time”, while the legal consequences arising is the time when the buyer does not exercise its right then right into the fall and selling into luzum (fixed).